2003
DOI: 10.1523/jneurosci.23-16-06510.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics of Rat Vibrissae: Resonant Frequencies and Damping in Isolated Whiskers and in the Awake Behaving Animal

Abstract: We investigated the natural resonance properties and damping characteristics of rat macrovibrissae (whiskers). Isolated whiskers rigidly fixed at the base showed first-mode resonance peaks between 27 and 260 Hz, principally depending on whisker length. These experimentally measured resonant frequencies were matched using a theoretical model of the whisker as a conical cantilever beam, with Young's modulus as the only free parameter. The best estimate for Young's modulus was approximately 3-4 GPa. Results of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
238
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(258 citation statements)
references
References 29 publications
19
238
0
1
Order By: Relevance
“…Measurements of Young's modulus of rat skin vary greatly, but 10 MPa is an order of magnitude estimate (Ozyazgan et al 2002); we therefore chose 10 MPa as an order of magnitude estimate for E of the follicle components. We chose all damping constants to critically damp their most closely associated mass, as measured whisker-FSC dynamic behaviours are in this region (Hartmann et al 2003). k MP was chosen to allow only limited follicle movement when the whisker is deflected, and the remaining constants were tuned to optimize the fit to observed data.…”
Section: Model Development (A) Overviewmentioning
confidence: 99%
“…Measurements of Young's modulus of rat skin vary greatly, but 10 MPa is an order of magnitude estimate (Ozyazgan et al 2002); we therefore chose 10 MPa as an order of magnitude estimate for E of the follicle components. We chose all damping constants to critically damp their most closely associated mass, as measured whisker-FSC dynamic behaviours are in this region (Hartmann et al 2003). k MP was chosen to allow only limited follicle movement when the whisker is deflected, and the remaining constants were tuned to optimize the fit to observed data.…”
Section: Model Development (A) Overviewmentioning
confidence: 99%
“…The morphological properties of the rat vibrissal system have been analysed in detail by Towal et al [22], Hartmann and co-workers [23] and Birdwell et al [24] who have shown that they make a significant contribution to the types of signals obtained through whisker-environment contacts. Here, we briefly discuss morphological features of biological vibrissal systems and their artificial counterparts together with sensor transduction and aspects of active sensing control.…”
Section: Introductionmentioning
confidence: 99%
“…At the point of entry to the system, the mechanical properties of the vibrissae likely impact the transduction of these sensory signals. For example, recent studies have shown that vibrissae resonate, generating a several fold increase in motion amplitude when stimulated at their fundamental resonance frequency (Neimark et al 2002;Hartmann et al 2003;Neimark et al 2003;Andermann et al 2004;Mehta and Kleinfeld 2004;Moore and Andermann 2005;Ritt et al, 2008). This pattern of frequency-specific transduction has recently been observed in animals freely sampling a variety of surfaces with their vibrissae (Ritt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Further, because vibrissa resonance is dependent on vibrissa length (Hartmann et al 2003;Neimark et al 2003), and length varies systematically from caudal to rostral across the vibrissa pad (Brecht et al 1997), a map of frequency-tuned neurons is overlaid on the somatotopic representation of vibrissa position. Along a dorsal-ventral arc, vibrissae have similar lengths and in turn similar frequency tuning, generating isofrequency 'columns' that span multiple vibrissarelated barrel columns in SI (Andermann et al 2004).…”
Section: Introductionmentioning
confidence: 99%